2019
DOI: 10.1111/all.14103
|View full text |Cite
|
Sign up to set email alerts
|

Immune complexes exposed on mast cell‐derived nanovesicles amplify allergic inflammation

Abstract: Ags. Studies are ongoing to compare nanovesicles derived from sera of atopic individuals before and during an acute phase of allergic reaction. Collectively, our data uncovered a new role for nanovesicles derived from activated MCs in the positive regulation of allergic responses, as depicted in our working model (Figure S6). Understanding how these nanovesicles influence the hypersensitivity reactions could help the development of more efficient therapies. ACK N OWLED G M ENTS This work was supported by the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 9 publications
2
31
0
Order By: Relevance
“…In this regard, we have previously reported in RBL-2H3 cells that upon antigen stimulation, FcεRIβ and γ subunits undergo ubiquitination, thus triggering receptor endocytosis from the cell surface to lysosomes for degradation [77,78] and envisaged a key role for the endocytic adapter Hrs [79]. More recently, we found that Hrs is required for exosome release by MCs, as well [51].…”
Section: Heterogeneity Of Mc-derived Evsmentioning
confidence: 74%
See 4 more Smart Citations
“…In this regard, we have previously reported in RBL-2H3 cells that upon antigen stimulation, FcεRIβ and γ subunits undergo ubiquitination, thus triggering receptor endocytosis from the cell surface to lysosomes for degradation [77,78] and envisaged a key role for the endocytic adapter Hrs [79]. More recently, we found that Hrs is required for exosome release by MCs, as well [51].…”
Section: Heterogeneity Of Mc-derived Evsmentioning
confidence: 74%
“…ESCRT complexes are composed of ESCRT-0 and ESCRT-I that promote cargo recruitment, while ESCRT-II and ESCRT-III, together with numerous accessory proteins, induce the inward budding of endosomal membrane and pinch off of ILVs. Notably, Hrs, a protein member of the ESCRT-0 complex, is critically involved in exosome biogenesis since its depletion on DCs, MCs, and HeLa cells strongly impairs nanovesicle secretion [51][52][53]. The ESCRT machinery also serves to ensure the proper composition of the vesicles.…”
Section: Extracellular Vesicles: Biogenesis and Compositionmentioning
confidence: 99%
See 3 more Smart Citations